Bkash Bangladesh: an innovative start for mobile financial services and its impact on long term poverty - Pranta, Abhishek Raha Roy (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.